Observations on selected characteristics of water and sediment at the open sea cage culture site of Asian seabass Lates calcarifer (Bloch) off Cochin, south-west coast of India - Prema, D.; Sobhana, K. S.; Laxminarayana, A.; Joseph, Imelda; Joseph, Shoji; Ignatius, Boby; Jeyabaskaran, R.; Nandakumar, A.; Khambadkar, L. R.; Anilkumar, P. S.; Shylaja, G.; Rao, G. Syda (Indian Journal of Fisheries, 2011)
Study was undertaken to assess the impact of open sea cage culture of Asian seabass Lates calcarifer on selected parameters of water as well as sediment at Munambam off Cochin, Kerala coast from November 2008 to March 2009. Periodic observations were made on temperature, pH, dissolved oxygen, salinity, nutrients (NO3, PO4, SiO3), nitrite, ammonia, BOD, total suspended solids, chlorophyll a, gross and net primary productivity as well as bacterial load of the surface and near bottom water from the cage site (N 10º 08' 162''; E 76º 08' 901'') and also from a reference site (N 10º 07' 189''; E 76º 09' 210'') during pre- as well as post-stocking periods. Sediment samples were collected simultaneously from both the sites and analysed for texture, pH, organic carbon and bacterial load. A significant reduction (p